2019
DOI: 10.1182/blood-2018-04-785899
|View full text |Cite
|
Sign up to set email alerts
|

How I treat refractory chronic graft-versus-host disease

Abstract: Approximately 35% to 50% of patients otherwise cured of hematologic malignancies after allogeneic hematopoietic stem cell transplantation will develop the pleomorphic autoimmune-like syndrome known as chronic graft-versus-host disease (cGVHD). Since in 2005, National Institutes of Health (NIH) consensus panels have proposed definitions and classifications of disease to standardize treatment trials. Recently, the first agent was approved by the US Food and Drug Administration for steroid-refractory cGVHD. Despi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 110 publications
0
56
0
3
Order By: Relevance
“…Partly, this was due to the single-agent PTCY prophylaxis protocol involving first line CsA for both acute and chronic GvHD, but also due national peculiarities of healthcare when a patient cannot easily travel to the transplant center and CNIs had to be introduced during distant consultations, while treatment with steroids were saved only for patients who could be admitted to the outpatient care. Secondly, there was an internal policy of faster steroid tapper after introduction of second line treatment than in the majority of centers [23]. Hence, if the patient did not show the signs of the flair he usually completely discontinued steroids within a month and continued only second line treatment, while the standard policy is to continue steroids until response.…”
Section: Discussionmentioning
confidence: 99%
“…Partly, this was due to the single-agent PTCY prophylaxis protocol involving first line CsA for both acute and chronic GvHD, but also due national peculiarities of healthcare when a patient cannot easily travel to the transplant center and CNIs had to be introduced during distant consultations, while treatment with steroids were saved only for patients who could be admitted to the outpatient care. Secondly, there was an internal policy of faster steroid tapper after introduction of second line treatment than in the majority of centers [23]. Hence, if the patient did not show the signs of the flair he usually completely discontinued steroids within a month and continued only second line treatment, while the standard policy is to continue steroids until response.…”
Section: Discussionmentioning
confidence: 99%
“…15 Given the uncertainties surrounding the biological basis of both acute and chronic GvHD and the lack of consensus around a standardized treatment approach, the harm profile of available treatments is a particularly important consideration for both healthcare providers and patients when balancing the benefits and risks of competing treatment options for post-allo-HSCT GvHD. 16 Whilst ruxolitinib was approved by the United States (US) Food and Drug Administration (FDA) for steroid-refractory aGvHD in May 2019, 17 standardised recommendations on how to best implement such a diverse array of treatments remain lacking. 18 The objective of this study was to review and describe reported harm outcomes associated with second-and third-line therapies for GvHD following allo-HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…found in the mouse models of pulmonary fibrosis post radiation that breathing air containing 4% H 2 has a significant therapeutic effect on chronic pulmonary fibrosis, and can significantly delay the progress of pulmonary fibrosis ( 13 ). Although the current mechanism of cGVHD is not very clear, in the currently recognized pathogenesis of cGVHD, inflammatory factors imbalance and fibrosis occupy a dominant position ( 4 , 14 ). Since H 2 has anti-inflammatory and anti-fibrosis effects, we speculate that H 2 may have potential therapeutic effects for cGVHD after allo-HSCT.…”
Section: Introductionmentioning
confidence: 99%